2008
DOI: 10.1002/jrs.2050
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐plane deformations of the heme group in different ferrocytochrome c proteins probed by resonance Raman spectroscopy

Abstract: We measured the low-wavenumber polarized resonance Raman spectra of horse heart (hhc), chicken (chc) and yeastC102T (yc) ferrocytochromes c with Soret excitation. We examined the out-of-plane (oop) deformations of the heme groups by virtue of relative intensities and depolarization ratios of a variety of oop and in-plane (ip) Raman active bands. Analysis of relative Raman intensities shows differences in deviation from planarity of the heme groups of yeast, horse heart and chicken cytochromes c. The heme group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…58 These spectral changes are sensitive to the structure of the substrate and the mutation in the H76 residue, demonstrating that the structural properties of the heme are closely coupled to the substrate through the H76 residue.…”
Section: Resultsmentioning
confidence: 96%
“…58 These spectral changes are sensitive to the structure of the substrate and the mutation in the H76 residue, demonstrating that the structural properties of the heme are closely coupled to the substrate through the H76 residue.…”
Section: Resultsmentioning
confidence: 96%
“…The much stronger intensity of the depolarized ν 15 band as compared to the polarized ν 7 band in WT is surprising. Recent studies conducted by Schweitzer-Stenner and coworkers suggest that the ν 15 band is a depolarized B 1g mode of a planar heme with D 4h symmetry; they showed that, if there is an in-plane distortion of the heme macrocycle, lowering the symmetry of the heme, the B 1g mode can be transformed into an A 1 mode, thereby gaining intensity in the resonance Raman spectrum [30]. Accordingly, we attribute the high relative intensity of the ν 15 band in the WT of PdC c O to an in-plane distortion of the heme a 3 , due to the interaction between the heme with its protein environment.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the type of OOP deformation is typically conserved within functionally-related classes of heme proteins 3. Ruffling is the principal OOP deformation in cytochrome c (cyt c ) electron transfer proteins,46 the enzyme-substrate complexes of heme oxygenases7 as well as the IsdG and IsdI heme-degrading enzymes,8 and the NO-carriers such as the nitrophorins and the heme nitric oxide/oxygen binding family of proteins 912. Saddling is prominent in peroxidases,13 while doming is typically observed in oxygen storage or transport proteins like myoglobin 14.…”
Section: Introductionmentioning
confidence: 99%